A Comparison Study: North Sumatera Young Counselor Perspective On Taboo Words - Tsaqilah, Fadhilah; Br. Perangin-Angin, Alemina (Peneliti.net, 2024)
Taboo words is really common in young generation because of the spread of technology and the lack of language education. As young counsellor experienced in every meeting with trainee young counsellor, there are found several taboo words that is specifically in genital words. This qualitative paper investigates three questions, namely: (1) What is taboo word in young counselor perspectives?; (2) What kind of taboo words used by young counselor during counseling?; (3) How do young counselors define and perceive taboo words in counselling. By interviewing young counsellors of BKKBN and the trainee, this paper shows that among young counsellors, the use of taboo words especially genital words is accepted in their culture because those are used in daily conversation, even though there are some trainee refuse the taboo words whether it is genital or cursed words. It is found that 12 cursed words and 13 genital words are spread in all over region in North Sumatera.